Characteristic adaptations of the extracellular matrix in dilated cardiomyopathy. (1st October 2016) - Louzao-Martinez, Laura; Vink, Aryan; Harakalova, Magdalena; Asselbergs, Folkert W.; Verhaar, Marianne C.; Cheng, Caroline
Abstract: Dilated cardiomyopathy (DCM) is a relatively common heart muscle disease characterized by the dilation and thinning of the left ventricle accompanied with left ventricular systolic dysfunction. Myocardial fibrosis is a major feature in DCM and therefore it is inevitable that corresponding extracellular matrix (ECM) changes are involved in DCM onset and progression. Increasing our understanding of how ECM adaptations are involved in DCM could be important for the development of future interventions. This review article discusses the molecular adaptations in ECM composition and structure that have been reported in both animal and human studies of DCM. Furthermore, we provide a transcriptome-based catalogue of ECM genes that are associated with DCM, generated by using NCBI Gene Expression Omnibus database sets for DCM. Based on this in silico analysis, many novel ECM components involved in DCM are identified and discussed in this review. With the information gathered, we propose putative pathways of ECM adaptations in onset and progression of DCM. Highlights: Dilated cardiomyopathy (DCM) involves extracellular matrix (ECM) adaptations. GEO datasets analysis reveals a novel transcriptome-based catalogue of ECM genes associated with dilated cardiomyopathy. ECM adaptations in DCM: 1) ECM synthesis and stabilization 2) fibroblast activity 3) collagens deposition 4) cell adhesion.